Development of an electronic system for remote communication in modbus RTU industrial devices via MQTT (COLOMBIAN JOURNAL OF ADVANCED TECHNOLOGIES, 2024)
This document presents the development process and initial testing phases of an electronic system designed to facilitate web-based communication for an industrial device. The industrial device operates using Modbus RTU communication, and the system utilizes the MQTT telemetry protocol, which is integrated into a 32-bit microcontroller. The microcontroller operates within a real-time operating system framework, ensuring efficient communication management. The system integration with a PLC has been established during the equipment development, and validation has been achieved through the utilization of a comprehensive database, Python scripts, and the incorporation of visualization capabilities provided by a web-based platform. The prototype is capable of remotely reading and modifying Modbus registers through a web interface, which not only allows parameter adjustments but also provides access to historical measurement records, enhancing the overall functionality of the industrial device.
Keywords: IIOT; MQTT; RTOS; Modbus; Microcontroller